Karakteristik dan Pengaruh Proses Sterilisasi terhadap Mutu Fisik Produk Lauk Berkuah dalam Kemasan Retort Pouch: Tinjauan Sistematis - Budi, Faleh Setia; Fadhillah, Azzam Akbar; Kusumaningrum, Harsi Dewantari (Universitas Trunojoyo Madura, 2024)
The development of ready-to-eat side dish products with gravy in retort pouches is based on the public's desire for quick, portable, and stable food options. This research aimed to examine the sterilization processes of side dish products with gravy in retort pouches, characterize these processes, and assess the influence of retort type on parameters of sterilization process and physical quality. The study was conducted via a literature review using specific keywords in journal search engines, resulting in secondary data from 10 articles covering 11 products and 26 sterilization processes. The products included 64% curry and other side dishes such as oil-based, masala, braised, and soup. Air-steam retort demonstrated superior heat penetration compared to water immersion retorts. The literature indicated that the sterilization process (commercial sterilization) typically used temperatures equivalent to 121℃ for 200–300 grams, with an F0 value exceeding the standard minimum of 3 minutes. Notable physical quality changes included a browner colour in curry products and improvements such as reduced stickiness in chicken curry mousse and a softer texture in curry.